Mixing Formal and Informal Model Elements for Tracing Requirements - Jastram, Michael; Hallerstede, Stefan; Ladenberger, Lukas (Electronic Communications of the EASST, 2012)
Tracing between informal requirements and formal models is challenging. A method for such tracing should permit to deal efficiently with changes to both the requirements and the model. A particular challenge is posed by the persisting interplay of formal and informal elements. In this paper, we describe an incremental approach to requirements validation and systems modelling. Formal modelling facilitates a high degree of automation: it serves for validation and traceability. The foundation for our approach are requirements that are structured according to the WRSPM reference model. We provide a system for traceability with a state-based formal method that supports refinement. We do not require all specification elements to be modelled formally and support incremental incorporation of new specification elements into the formal model. Refinement is used to deal with larger amounts of requirements in a structured way. We provide a small example using Problem Frames and Event-B to demonstrate our approach.